2021
DOI: 10.3390/su13137458
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Emotional Solidarity in the Homestay Industry between Hosts and Tourists in the Post-Pandemic Era

Abstract: Tourists’ perceptions of various risks at their travel destinations have crucial implications for destination management organizations and other tourism industry practitioners, which is growing into an unprecedented concern in the post-pandemic era. The Internet has boosted the global homestay industry. The perceived risk of homestay tourists requires further attention from researchers to promote the sustainable development of the homestay industry, especially in the post-pandemic era. To supplement and enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
(89 reference statements)
6
19
0
1
Order By: Relevance
“…On the basis of their enhanced emotional identification, these tourists’ desire to revisit, recommend, provide support, and enjoy a similar satisfying experience may influence their future tourism decisions. This study also reaffirms the previous finding that the ES between tourists and homestay inn hosts increases the latter’s intensity of revisiting, recommending, or providing support at the destination [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…On the basis of their enhanced emotional identification, these tourists’ desire to revisit, recommend, provide support, and enjoy a similar satisfying experience may influence their future tourism decisions. This study also reaffirms the previous finding that the ES between tourists and homestay inn hosts increases the latter’s intensity of revisiting, recommending, or providing support at the destination [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, customers paid less attention to the value, especially the price, indicating that customers were not sensitive to the prices of either type of B&B. To some extent, this echoes another study [17], which indicated that B&Bs in China are high-end accommodation products and a symbol of luxury, which makes customers more focused on social value than on functional value [17]. Therefore, the price is not an important consideration.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, they need to built connections with their hosts. Furthermore, there is literature that shows that the emotional closeness between customers and hosts is the factor most important in business success [17], so hosts should also strengthen their relationships with their customers to improve customer satisfaction. Furthermore, we also found that the convenience of urban B&Bs is more prominent than that of rural B&Bs from the customer perspective, which also verifies the customers' view of the location superiority of urban B&Bs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived risk refers to the spirit cost associated with customers’ purchasing behavior, which significantly impacts tourist behavior ( Nguyen et al, 2021 ). Tourists’ perceived risk is highly correlated with their experience and loyalty ( Zhang and Tang, 2021 ). When their perceived risk is low, they are more at ease with bicycle-sharing and more inclined to become loyal, whereas, when they have a higher risk perception, they tend to be less loyal and refuse to reuse ( Jin et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%